10.6k views
2 votes
8(t+2)-3(t-4)=6(t-7)+8 i dont understand this is 5.111111 correct?

User Derk
by
5.1k points

1 Answer

3 votes
8(t + 2) - 3(t - 4) = 6(t - 7) + 8

To solve this equation, first apply the Distributive Property. The Distributive Property is defined as a(b + c) = ab + ac. We'll need to apply it three times for this equation.

8(t + 2) => 8t + 16
-3(t - 4) => -3t + 12
6(t - 7) => 6t - 42

This gives us

8(t + 2) - 3(t - 4) = 6(t - 7) + 8
8t + 16 - 3t + 12 = 6t - 42 + 8

Next, combine like terms (constants with constants and variable terms with variable terms).

8t + 16 - 3t + 12 = 6t - 42 + 8
5t + 28 = 6t - 34

Now we need to get all constants on one side and all variable terms on the other side. Begin doing so by first subtracting 28 from both sides.

5t + 28 = 6t - 34
5t = 6t - 62

Subtract 6t from both sides.

5t = 6t - 62
-t = -62

Divide both sides by -1.

t = 62

Answer:
t = 62
User Mittenchops
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.